2013
DOI: 10.1111/hae.12127
|View full text |Cite
|
Sign up to set email alerts
|

Product‐dependent anti‐factor VIII antibodies

Abstract: Introduction The development of anti-factor (F)VIII antibodies in hemophilia A (HA) subjects undergoing replacement therapy has been well-documented. The correlation between antibody development and the FVIII product used for replacement therapy remains a subject of discussion. Aim To evaluate the presence of anti-FVIII antibodies toward three commercial rFVIII products in 34 HA subjects’ plasmas. Methods Antibodies were quantitated by a Multiplex Fluorescence Immunoassay. Results All plasmas contained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…Coagulation factor replacement therapy usually starts at a very young age and requires regular intravenous dosing for the patient's lifetime. The development of inhibiting antibodies to replacement FVIII and FIX is one of the clinical concerns in treatment of hemophilia . These inhibitors block the function of the proteins and can be life‐threatening.…”
Section: Host Cell Cytokine Impuritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Coagulation factor replacement therapy usually starts at a very young age and requires regular intravenous dosing for the patient's lifetime. The development of inhibiting antibodies to replacement FVIII and FIX is one of the clinical concerns in treatment of hemophilia . These inhibitors block the function of the proteins and can be life‐threatening.…”
Section: Host Cell Cytokine Impuritiesmentioning
confidence: 99%
“…The development of inhibiting antibodies to replacement FVIII and FIX is one of the clinical concerns in treatment of hemophilia. 53,54 These inhibitors block the function of the proteins and can be life-threatening.…”
Section: Hcps In Hemophilia Therapeuticsmentioning
confidence: 99%
“…17 Regarding nonneutralizing antibodies, it remains debated as to whether these antibodies, or at least any immune response they provoke, are of clinical significance and should be considered as well. [18][19][20] The importance of T-regulatory cells (Tregs) in the process of antibody formation has been established, and to date, different subsets of cells with suppressor activities have been defined, eg, CD4 …”
mentioning
confidence: 99%
“…Non-neutralizing antibodies have been described in haemophilia patients but their significance has not been elucidated [11,12]. Studies in other diseases indicated that NNA against therapeutic proteins may alter the protein's PK profiles [13].…”
mentioning
confidence: 99%